The interaction of host and nematode galectins influences the outcome of gastrointestinal nematode infections. Issue 6 (19th May 2021) - Donskow-Łysoniewska, Katarzyna; Maruszewska-Cheruiyot, Marta; Stear, Michael
Abstract: Abstract: Galectins are a family of proteins that bind β -galactosides and play key roles in a variety of cellular processes including host defence. They have been well studied in hosts but less so in gastrointestinal nematodes. Both host and parasite galectins are present in the gastrointestinal tract following infection. Parasite galectins can both bind antibody, especially highly glycosylated IgE and be bound by antibody. Parasite galectins may act as molecular sponges that soak up antibody. Host galectins promote mast cell degranulation while parasite galectins inhibit degranulation. Host and parasite galectins can also bind mucins and influence mucus viscosity. As the protective response against gastrointestinal nematode infection is partly dependent on IgE mediated mast cell degranulation and mucus, the interactions between host and parasite galectins play key roles in determining the outcome of infection.